DETERMINAN INVESTASI DI DAERAH: STUDI KASUS PROPINSI DI INDONESIA - Jamzani Sodik; Didi Nuryadin (Universitas Islam Indonesia, 2008)
The main purpose of this research is to test the determinant of investment locations in 26 provinces in Indonesia between 1993-2003 using dynamics method of panel. Factors affecting to investment locations in Indonesia are indicator of market size which is growth rate PDRB (X1), infrastructure indicator i.e. number of electricity capacity (X2), indicator spatial which is deensity (X3), indicator manpower that is labour force (X4) and wages/UMP (X5), and last of economic indicators that is export/ level of chartered investment counsel openness (X6). The result concludes that all variables applied in stationary research has at data level (I0), equally all variables have owned degree of the same integration. Result of testing of panel co integration with approach of parametric indicates that Group rho-Statistic to have coefficient 8432 while Group PP-Statistic has coefficient co integration of 9193. The coefficient co integration by using Group ADF-Statistic is 2540. Probability each testing method indicates that variable applied by co integrating at level of significance at 5%. From total 7 testing panel, got result that all research variable of co integrating or on a long term research variable has direction of the same movementKeywords: investments, panel dynamic, unit root panel, and cointegration panel